Diabetes status modifies the association between carotid intima-media thickness and incident heart failure: The Atherosclerosis Risk in Communities study. (June 2017) - Effoe, Valery S.; McClendon, Eric E.; Rodriguez, Carlos J.; Wagenknecht, Lynne E.; Evans, Gregory W.; Chang, Patricia P.; Bertoni, Alain G.
Highlights: Association between carotid IMT and heart failure stronger in persons without diabetes. Rates of heart failure disproportionately higher in persons with diabetes. No black-white differences in association between carotid IMT and heart failure across diabetes status. Abstract: Aims: Increasing carotid intima-media thickness (CIMT) is associated with incident heart failure (HF). We investigated whether this association differs by diabetes status. Methods: We characterized 13, 590 Atherosclerosis Risk in Communities Study participants free of baseline HF into normal fasting glucose (NFG, glucose <100 mg/dl), impaired fasting glucose (IFG, glucose 100–125 mg/dl), and type 2 diabetes (T2D, glucose ≥126 mg/dl, self-report, or use of diabetes drugs). CIMT was assessed by B-mode ultrasound. Incident HF was defined using ICD-9 or 10 codes from hospitalizations and death certificates. Cox regression was used to estimate hazard ratios (HR) for incident HF, adjusting for age, sex, race, education, hypertension medication, blood pressure, BMI, waist circumference, HDL, LDL, triglycerides, lipid-lowering medication, smoking, alcohol, serum creatinine, and interim CHD. Results: T2D participants had higher mean CIMT (0.79 ± 0.20 mm), compared to IFG (0.75 ± 0.19 mm) and NFG (0.70 ± 0.17 mm) ( p  < 0.0001). Over 20.6 years of median follow-up, 15% developed HF. Rates of HF (per 1000 person-years) were substantially higher for those with T2D (24.7), compared to IFG (7.7) and NFG (5.8). In adjusted analyses, the CIMT-HF association was significantly modified by diabetes status ( P interaction  = 0.015): for NFG (HR per SD increase in CIMT: 1.27; 95%CI: 1.20–1.34), IFG (HR 1.18; 95%CI: 1.11–1.25) and T2D (HR 1.12; 95%CI: 1.05–1.21). Conclusions: CIMT is associated with increased risk of HF, particularly among persons without diabetes. Due to a high absolute risk of HF among adults with T2D, CIMT may be a less reliable predictor.